'They came from the ends of the earth': long-distance exchange of obsidian in the High Arctic during the Early Holocene. (18th February 2019) - Pitulko, Vladimir V.; Kuzmin, Yaroslav V.; Glascock, Michael D.; Pavlova, Elena Yu.; Grebennikov, Andrei V.
Abstract: Abstract : Zhokhov Island in the Siberian High Arctic has yielded evidence for some of the most remote prehistoric human occupation in the world, as well as the oldest-known dog-sled technology. Obsidian artefacts found on Zhokhov have been provenanced using XRF analysis to allow comparison with known sources of obsidian from north-eastern Siberia. The results indicate that the obsidian was sourced from Lake Krasnoe—approximately 1500km distant—and arrived on Zhokhov Island c . 8000 BP. The archaeological data from Zhokhov therefore indicate a super-long-distance Mesolithic exchange network.